Proust Cinématographe Wie Raoul Ruiz Proust las - Jaritz, Joanna (Heidelberg University Publishing (heiUP), 2017)
"Proust Cinematographe - Ruiz reading In Search of Lost Time" takes a new look at the metapoetic program of Proust's A la Recherche du Temps perdu. Selected text passages and film excerpts are analyzed, focusing on the fundamental questions of the novel about the perception and description of time, subject, and identity. It turns out that the novel of the nineteenth century anticipated the concepts of modern cinema on a surprisingly broad scale.